Association of the VEGF 936C>T polymorphism with FDG uptake, clinical, histopathological, and metabolic response in patients with adenocarcinomas of the esophagogastric junction - Lorenzen, Sylvie; Panzram, Benjamin; Keller, Gisela; Lordick, Florian; Herrmann, Ken; Becker, Karin; Langer, Ruppert; Schwaiger, Markus; Siewert, Jorg Rudiger; Ott, Katja (Molecular imaging & biology, 2011)
The MUNICON trial confirmed prospectively the usefulness of early response evaluation by 2-deoxy-2-[F-18]fluoro-D-glucose-positron emission tomography (FDG-PET) . Metabolic responders (R) showed initially a higher FDG uptake compared with nonresponders (p = 0.018). An association of the vascular endothelial growth factor (VEGF) 936C>T polymorphism and FDG uptake was reported for breast cancer. Therefore, we investigated the VEGF 936C>T polymorphism for an association with response and survival.